BIOFILMS AND THEIR ROLE IN INFECTIOUS DISEASES - V.V. Nedashkivska; M.L. Dronova; N.O. Vrynchanu (Bogomolets National Medical University, 2016)
The formation of biofilms - organized microbial communities, is one of the main strategies for their survival, not only in the environment, but also in macroorganism. Research in this area has captured a close attention of scientists, because the ability of pathogenic bacteria to pellicle formation results in considerable clinical problems, e.g., significant increase of pathogen resistance to antimicrobials and host defense factors. It is currently established, that biofilms are characterized by gradual development, presence of extracellular matrix and self-regulation by cell-to-cell communication (quorum sensing system), thereby, novel targets for antibiofilm therapy are presented. Biofilm microorganisms predominantly cause chronic diseases, but in the case of dissemination and release of planktonic forms can also exacerbate inflammatory processes. Biofilms, formed by bacteria, fungi or microbial associations colonize wounds, cause ENT diseases, soft tissue and bone infections, respiratory, urinary, cardiovascular disorders, inflammation of reproductive system, gastrointestinal tract, etc. It is proved now, that microorganisms are able to form biofilms not only on biotic, but on abiotic surfaces as well. Particularly important infections are associated with medical devices, e.g., catheters, stents, artificial valves, as biofilm could be found on their surface even in the first days after placing. Detailed studies of the biofilm properties significantly upgrade our understanding of relationship of bacteria and fungi with the human body, infection mechanisms and the patterns of antimicrobials' action on microorganisms. These data provide immense opportunities for medical microbiology, clinical and experimental pharmacology to develop new approaches for diagnosis and treatment of biofilm infections.